2017
DOI: 10.1021/acs.organomet.7b00511
|View full text |Cite
|
Sign up to set email alerts
|

Nondissociative Mechanism for the Inversion of the Configuration in Cyclopentadienyl Di(aryloxo)titanium Complexes: An Entropy Discussion

Abstract: Titanium complexes with two dioxo bridges between the Cp and the metal can be synthesized by the reaction of [Ti{η 5 -C 5 H 3 -1,3-(SiMe 2 Cl) 2 }Cl 3 ] with different diols. Some of these complexes present a dynamic inversion process affording two diastereomers, A and B, which have been studied by X-ray diffraction and NMR techniques. The X-ray diffraction studies of [Ti{η 5 -C 5 H 3 -1,3-[SiMe 2 (κ 1 -1,2-O 2 C 6 H 4 )] 2 }X] X= Cl (2A), Me (4A), and Bn (5) complexes permit their absolute configuration to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Stereomutation of tetracoordinate species is seen with titanium tetracoordinate complex 51 (Scheme ). Crucially, Cano et al . argued against a dissociative mechanism on the basis of crossover experiments and a lack of solvent polarity dependence for the rate of exchange.…”
Section: Intramolecular Stereomutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereomutation of tetracoordinate species is seen with titanium tetracoordinate complex 51 (Scheme ). Crucially, Cano et al . argued against a dissociative mechanism on the basis of crossover experiments and a lack of solvent polarity dependence for the rate of exchange.…”
Section: Intramolecular Stereomutationsmentioning
confidence: 99%
“…Stereomutation of tetracoordinate species is seen with titanium tetracoordinate complex 51 (Scheme 16). Crucially,C ano et al [86] argued against ad issociative mechanism on the basis of crossovere xperiments and al ack of solvent polarity dependence fort he rate of exchange. As eries of 1 H-1 HE XSY experiments were performed to determine the first-order rate constant for this process, and an Eyring plot was used to derive DS ¼ 6 ,which, in agreement with anon-dissociative mechanism,w as as mall negative number.T he authors propose a turnstile-like rotation in which the Xa tom and the apical LUMO rotate as ap air,w hereas the tridentate ligand rotates as at rio.…”
Section: Tetracoordinate Centresmentioning
confidence: 99%
“…For many systems in which host-guest exchange occurs (involving hemicarcerands, cucurbiturils, and metal-ligand frameworks) it has been reported that the activation entropy is slightly negative or close to zero for associative processes, and positive for dissociative processes. [30][31][32][33][34][35][36] For our host-guest systems this would tentatively indicate that exchange occurs through an associative mechanism.…”
Section: Mechanism Of the Exchange Processmentioning
confidence: 72%
“…The fluxionality due to the hemilabile coordination of the donor-functionalized alkoxide ligands can cause the nitrogen and gallium atoms to dissociate–associate in a dynamic fashion, producing the broad spectrum observed at 296 K (Figure ). This fluxionality displayed by compounds 2 and 3 is not surprising; five-coordinate trigonal bipyramidal systems are capable of polytopal rearrangements in the coordination sphere, classically portrayed by PF 5 , with more modern examples including titanium, cobalt, iron, and antimony complexes. Following these types of rearrangements, bidentate ligands with weakly coordinated donor groups lying in the axial positions could plausibly undergo dissociation, when bound to a labile metal centerin this case, gallium­(III). This disconnection from either one or both of the hemilabile alkoxide ligands allows an inversion of the configuration at the metal center, followed by reattachment of the two nitrogen-donor groups.…”
Section: Results and Discussionmentioning
confidence: 99%